F2A sequence linking MGMT P140K and MDR1 in a bicistronic lentiviral vector enables efficient chemoprotection of haematopoietic stem cells - Maier, Patrick; Heckmann, Doreen; Maier-Laufs, Stephanie; Wenz, Frederik (Cancer gene therapy, 2012)
Chemoprotection of haematopoietic stem cells (HSCs) by gene therapeutic transfer of drug-resistance genes represents the encouraging approach to prevent myelosuppression, which is one of the most severe side effects in tumor therapy. Thus, we cloned and evaluated six different bicistronic lentiviral SIN vectors encoding two transgenes, MGMTP140K (an O6-benzylguanine-resistant mutant of methylguanine-DNA methyltransferase) and MDR1 (multidrug resistance 1), using various linker sequences (IRESEMCV, IRESFMDV and 2A-element of FMDV (F2A)). Expression of both transgenes in HL-60 and in K562 cells was assayed by quantitative real-time PCR. Combination therapy with ACNU plus paclitaxel in HL-60 cells and with carmustin (BCNU) plus doxorubicin in K562 cells resulted in the most significant survival advantage of cells transduced with the lentiviral vector HR’SIN-MGMTP140K-F2A-MDR1 compared with untransduced cells. In human HSCs, overexpression of both transgenes by this vector also caused significantly increased survival and enrichment of transduced cells after treatment with BCNU plus doxorubicin or temozolomide plus paclitaxel. In summary, we could show significant chemoprotection by overexpression of MDR1 and MGMTP140K with a lentiviral vector using the F2A linker element in two different haematopoietic cell lines and in human primary HSCs with various combination regimens. Consequently, we are convinced that these in vitro investigations will help to improve combination chemotherapy regimens by reducing myelotoxic side effects and increasing the therapeutic efficiency.
"P140K" ist im Titel hochgestellt
Gesehen am 16.08.2018